Memupuk Atensi Peduli Lingkungan melalui Pelatihan Ecoprint di MTs Inklusi Bontocinde - Ian Alfian; Fitha Armeinty Lino Padang; Sitti Rahma Yunus; Ramlawati Ramlawati; Amalia Safitri (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
Inorganic waste has become a serious problem and affects the balance of life. One of the inorganic wastes that pollute the environment is single-use plastic bags. An education is needed to reduce pollution, so ecoprint training is conducted at MTs. Bontocinde inclusions. The aim of the ecoprint training is to pay attention to environmental care behavior. The output of this training is ecoprint tote bags and the level of satisfaction of students participating in ecoprint training. The methods used in this activity are socializing activities, training on making ecoprint products, and program evaluation. The training was conducted for 2 days at MTs Inclusion Bontocinde, Gowa Regency. The results of the ecoprint training are ecoprint totebags and student satisfaction is at 80%, namely at the agree level. This indicates that students are satisfied and agree to carry out environmental care behaviors.